Waste Management at Construction Sites in the Municipality of Manaus, Amazonas, Brazil: Characterization of the Current Situation - Oliveira, Maria (2019)
This research aimed the characterization of the current production of construction waste in the city of Manaus, Amazonas, Brazil, and its impacts on the environment of the Amazon Region. The significance of this research work is to contribute to the improvement of the environmental management of waste in the construction sites of the city of Manaus, with the aim of preserving the Amazonian environment. This research also sought to characterize the existing problems in the environmental management of construction waste in four construction sites, with areas greater than 9,000 square meters. The methodology adopted was based on the application of an in situ survey in four construction sites in the city of Manaus, Amazonas, Brazil, administered by three companies representing the construction sector in the Amazon Region. Data were collected at the construction sites in question in the second half of 2018, regarding the types of construction waste produced, respective volumes, destination and associated costs. A comparison was made between constructed areas and volumes of waste produced, characterizing the current situation of construction waste production in the city of Manaus. After analysing the results obtained, it was concluded that due to the high associated costs, companies avoid recycling construction waste, and opt to discharge it in municipal or clandestine landfills, with significant environmental impacts. For this reason, a greater participation of the Public Administration is recommended regarding the adequate management of waste in construction sites, namely offering financial incentives for companies to promote the recycling and reuse of construction waste.